2012
DOI: 10.1021/nl3037867
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enhanced Exciton Recombination Rate by Strong Electron–Phonon Coupling in Single ZnTe Nanobelt

Abstract: Electron-phonon coupling plays a key role in a variety of elemental excitations and their interactions in semiconductor nanostructures. Here we demonstrate that the relaxation rate of free excitons in a single ZnTe nanobelt (NB) is considerably enhanced via a nonthermalized hot-exciton emission process as a result of an ultrastrong electron-phonon coupling. Using time-resolved photoluminescence (PL) spectroscopy and resonant Raman spectroscopy (RRS), we present a comprehensive study on the identification and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 55 publications
5
57
2
1
Order By: Relevance
“…The plasmonic cavities exhibit ultrasmall modal volume V m Bl 3 / 10-l 3 /1,000 (l is wavelength) enabling the tailoring of the strong light-matter interaction in a variety of linear (BQ/V m ) and nonlinear (BQ 2 /V m or Q/V m 1/2 ) optical process, where Q is the cavity quality factor. However, due to high intrinsic metal ohmic losses and radiation leakage, particularly in visible and ultraviolet regime, the Q ranges B10-100 which is still much smaller than their dielectric counterpart [20][21][22][23] . As a result, the threshold of optical-pumped visible plasmonic lasing (400-700 nm) is still nearly three orders higher than II-VI/III-VI semiconductor nanostructure photonic lasing.…”
mentioning
confidence: 99%
“…The plasmonic cavities exhibit ultrasmall modal volume V m Bl 3 / 10-l 3 /1,000 (l is wavelength) enabling the tailoring of the strong light-matter interaction in a variety of linear (BQ/V m ) and nonlinear (BQ 2 /V m or Q/V m 1/2 ) optical process, where Q is the cavity quality factor. However, due to high intrinsic metal ohmic losses and radiation leakage, particularly in visible and ultraviolet regime, the Q ranges B10-100 which is still much smaller than their dielectric counterpart [20][21][22][23] . As a result, the threshold of optical-pumped visible plasmonic lasing (400-700 nm) is still nearly three orders higher than II-VI/III-VI semiconductor nanostructure photonic lasing.…”
mentioning
confidence: 99%
“…The luminescence at variable excitation energies revealed that the spectrum was mediated by phonons in a hot-luminescence process. They also measured the temperaturedependent spectroscopy and confirmed the hot-luminescence [56].…”
Section: Breakdown Of Molecular Electronic Dynamics By Ultrafast Plasmentioning
confidence: 69%
“…This light emission means that the molecular electronic dynamics deviate from those in a free space by a large EM enhancement effect. This deviation indicates the breakdown of conventional molecular electronic dynamics by plasmonic de-excitation, and it has been investigated as the ultra-fast emission of light [42,48,[52][53][54][55][56]. II.…”
Section: Necessity Of Re-examination Of the Electromagnetic Mechanismmentioning
confidence: 99%
See 2 more Smart Citations